Sámi Art and Aesthetics: Contemporary Perspectives - Aamold, Svein (Aarhus University Press, 2017)
During the last five decades we have witnessed an increase in activity among artists identifying themselves as Sami, the only recognised indigenous people of Scandinavia. At the same time, art and duodji (traditional Sami art and craft) have been organized and institutionalized, not least by the Sami artists themselves.
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé